2005
DOI: 10.1590/s1516-635x2005000200010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deboning time on the quality of broiler breast meat (Pectoralis major)

Abstract: The present study evaluated the effect of different deboning times on the quality of broiler breast meat. Seventy-two broiler breasts were evaluated. They were distributed in a completely randomized experimental design, with six treatments, six repetitions and two birds per parcel. The treatments were denominated as follows: A - deboning immediately after chilling, B - deboning 1 h after chilling, C - deboning 2 h after chilling, D - deboning 3 h after chilling, E - deboning 4 h after chilling, and F - debonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
3
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
(18 reference statements)
6
3
1
4
Order By: Relevance
“…It was observed that the tenderness improved, with increasing time of 6 hours deboning time, in agreement with Thielke et al (2005) that suggested deboning time of minimum 6 hours in order to obtain tender texture. Regardless of the deboning time, the treatments with holding time of 24 hours were evaluated as more tender than the standard (treatments 3, 6 and 9), wich is in agreement to other authors (LYON et al, 1992;LIU et al, 2004;PETRACCI et al, 2001;SOUZA et al, 2005;HUEZO et al, 2007;BATULLA et al, 2008;THIELKE et al, 2005), that reported an increase in tenderness, as ageing time increased before and after the deboning.…”
Section: Sartori T C and Terra N Nsupporting
confidence: 89%
See 2 more Smart Citations
“…It was observed that the tenderness improved, with increasing time of 6 hours deboning time, in agreement with Thielke et al (2005) that suggested deboning time of minimum 6 hours in order to obtain tender texture. Regardless of the deboning time, the treatments with holding time of 24 hours were evaluated as more tender than the standard (treatments 3, 6 and 9), wich is in agreement to other authors (LYON et al, 1992;LIU et al, 2004;PETRACCI et al, 2001;SOUZA et al, 2005;HUEZO et al, 2007;BATULLA et al, 2008;THIELKE et al, 2005), that reported an increase in tenderness, as ageing time increased before and after the deboning.…”
Section: Sartori T C and Terra N Nsupporting
confidence: 89%
“…The consumer concern about food safety and convenience has increased the demand for fully cooked products (LEONHARDT et al, 2004;SOUZA et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this condition is predominantly observed in beef cattle, it also occurs in other meat species (Warriss et al, 1984(Warriss et al, , 1989Allen et al, 1997). In broiler chicken, breast muscle usually exhibits an elevated ultimate pH (pH > 5.9) 20 (Qiao et al, 2001;Alvarado and Sams, 2002;Souza et al, 2005;Zhu et al, 2013), however, DFD does not appear to be a major problem for the poultry industry (Qiao et al, 2001;Lesiów and Kijowski, 2003). This is likely due to the low concentration of myoglobin 25 in broiler breast muscle (Nishida and Nishida, 1985;Boulianne and King, 1995), which may prevent meat color darkening.…”
Section: Introductionmentioning
confidence: 99%
“…Resultado bem distinto ao encontrado neste trabalho o que pode ser relacionado a diferente metodologia empregada pelo pesquisador e pelas etapas "ante" e "post-mortem" a que as aves foram submetidas. Para Souza et al (2005) que analisaram a carne de peito de frangos, diferentes períodos de desossa da carne após o resfriamento da carcaça não afetaram significativamente as perdas por cocção.…”
Section: Ns: Significant Level; Cv: Coefficient Of Variation Means Iunclassified